Adhesion mechanism of cold-sprayed Sn coatings on carbon fiber reinforced plastics - Sun, Jiayu; Yamanaka, Kenta; Zhou, Shaoyun; Saito, Hiroki; Ichikawa, Yuji; Ogawa, Kazuhiro; Chiba, Akihiko (Applied surface science, 2022)
[Display omitted] •Adhesion mechanism of cold-sprayed Sn coatings on CFRPs was investigated.•Specimens were prepared at gas temperatures of 473 and 523 K.•Mechanical interlocking is the primary adhesion mechanism at 473 and 523 K.•Pull-off tests were conducted to evaluate the adhesion strength.•The specimen deposited at 523 K exhibited a higher adhesion strength.•The surface temperature of the specimen at 473 K is lower than the glass transition temperature of epoxy, while higher at 523 K. Metallization of carbon fiber reinforced plastics (CFRPs) has been explored to improve the electrical and thermal conductivities for avoiding thermal degradation and preventing lightning strikes on aircraft. In our recent study, Sn was successfully deposited on a thermosetting-based CFRP using cold spraying. Therefore, this study investigated the adhesion mechanism of the cold-sprayed Sn coatings on the CFRPs prepared at different gas temperatures (473 and 523 K). Herein, pull-off tests were conducted on the specimens deposited at 473 and 523 K, and the obtained results implied that the adhesion strength for the specimen deposited at 523 K was higher. In addition, cross-sectional and superficial observations were carried out after the pull-off test. The obtained results suggest that the chemical reactions between the Sn coating and CFRP substrate hardly occurred during cold spraying. Therefore, mechanical interlocking was considered as the primary mechanism of adhesion. The surface of the CFRP substrate degraded owing to the impacts of stronger particles at higher gas temperatures, representing complex interfacial morphologies that comprise exposed carbon fibers. The resultant rougher surfaces could enhance the mechanical interlocking at the Sn/CFRP interface, thereby improving the adhesion strength.